Sensorless angle and stiffness control of antagonistic PAM actuator using reference set. (3rd May 2022) - Shin, Takaya; Kogiso, Kiminao
Abstract : This paper proposes a simultaneous control method for the angle and stiffness of the joint in an antagonistic pneumatic artificial muscle (PAM) actuator system using only pressure measurements in the absence of an external force, and clarifies the allowable references for the PAM actuator system. To achieve a sensorless control, the proposed method estimates the joint angle and contraction forces using an unscented Kalman filter that employs a detailed model of the actuator system. Unlike the previous control methods, the proposed method does not require any encoder and force sensor to achieve angle and stiffness control of the PAM actuator system. Experimental validations using three control scenarios confirm that the proposed method can control the joint angle and stiffness simultaneously and independently. Moreover, it is shown that a reference admissible set can be used as an indicator to establish the reference values by demonstrating that the reference set covers the experimentally obtained trajectories of the angle and stiffness. GRAPHICAL ABSTRACT: UF0001